Determination of Suitable Groundwater Quality for Agriculture By Using GIS Application, Bantul Regency, Yogyakarta Special Province, Indonesia - Chhuon Kong, Chhuon Kong (2013)
In order to evaluate groundwater quality for irrigation purpose within Bantul area situated on Yogyajarta-Sleman Groundwater Basin, 77 data points of groundwater quality within the study area were used. The relative tendency of ion in epm shows Ca2+>K+>Na+>Mg2+ and HCO3->Cl->SO42-. Variations in groundwater composition using Mg/Ca vs Na/Ca in molar ratio, inidicates groundwater is close to silicate rock with influence of clastic carbonate rock. Higher salinity approach to the west of the Bantul, indicates that groundwater quality i controlled by clastic carbonate rock of Sentolo Hills. Groundwater fall under class I suggested that is good and suitable for irrigation based on Doneen's classification od Permeability Index and 78.37% is in excellent category by Wilcox classification on Sodium Percentage (Na%). According to the Sodium Adsorption Ratio (SAR) plotted in the USSL diagram, the majority of the groundwater samples belong to class C2-S1 and C2-S2, indicating medium salinity and low sodium water which can be used for irrigation with little danger. Salinity is the significant problem has slight to moderate restriction on crops productivities. The ECw map indicates good groundwater quality for agricluture is determined by using ArcGIS Spatial Analyst based on FAO guideline. The slight to moderate restriction on sensitive crops indicating with different yield potential in the agricultural land in which 100%, 90%, and 75% of yield potential correspond to about 2727.90 ha, 735,49 ha and 208.98 ha of the study area respectively